If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = -1.72 Reorder the terms: -3 + 4x = -1.72 Solving -3 + 4x = -1.72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 4x = -1.72 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = -1.72 + 3 4x = -1.72 + 3 Combine like terms: -1.72 + 3 = 1.28 4x = 1.28 Divide each side by '4'. x = 0.32 Simplifying x = 0.32
| 6s+6=-4 | | 4x(6-3)=94 | | -3n-9=0 | | 16m^4+9n^4=0 | | 375=4p-175 | | 8-7x=8(1+7x) | | (0.5*2.5)*x=3.5 | | 4(6-3)=94 | | -10=-9+x/4 | | 4x-3=1.72 | | r^3-11r^2+36r-36= | | 7m-6=65 | | 9-3r=2h | | -5(x-4)-3(-2-x)=x-2 | | 42+17r=-14r+-42 | | 4.2+2=10 | | 180=7x-13+2x+2+4x+9 | | 8=5-3x-6 | | X-5=2x-24 | | -25=5(w-7)-7w | | 4u^4+68u^2+280=0 | | 8=4-6b+2b | | 15=6-3n | | 72yp-12y= | | 5x+500=150 | | -9=3+5a-7 | | -4.9x^2+7.4x+10.9=0 | | 190=7x-13+2x+2+4x+9 | | 5y+13+5-3y=m | | 4(2y-4)=2(y-13) | | 60-(3c+4)=4c+24+c | | 14-6x= |